Educação em escola ribeirinha de Abaetetuba: afetividade como condição de aprendizagem - SILVA, Hudson Pantoja da (2019)
The present work aims to reflect on the importance and contribution of affectivity in the teaching-learning process, highlighting the need to bring to the school environment a pleasant coexistence among all those involved in it, contributing to the integral formation of the child. In this work we will use some conceptions of affectivity and some considerations about Early Childhood Education. As a theoretical basis, we rely on some theorists related to the subject, such as Vygotsky (1998), Piaget (1996), Monte-Serrat (2007), Davis and Oliveira (1994), Cazaux (1995), among others. This is a qualitative study conducted through field observations and interviews with the research participants. The results of the study showed that: 1- Although there are teachers who are committed to teaching beyond the transmission of scientific knowledge and who consider cultural and regional knowledge to be important, there is still much to be developed in relation to this bias educational. 2- There is no denying the connection between affectivity and learning, because in school the child relates emotionally to all the individuals who are part of the teaching / learning system, which leads us to reflect on the need to to rescue this theme in pedagogical action as a facilitator of the teaching-learning process. 3- Even with all the problems that this study verified, it can be affirmed that it is possible to establish good relations between teacher-student, school-community and studentstudent.